A Comparative Study of Multiparametric MRI Sequences in Measuring Prostate Cancer Index Lesion Volume. Issue 1 (10th November 2022) - Bagcilar, Omer; Alis, Deniz; Seker, Mustafa; Erdemli, Servet; Karaarslan, Umut; Kus, Aylin; Kayhan, Cavit; Saglican, Yesim; Kural, Ali; Karaarslan, Ercan
Objectives: To compare the effectiveness of individual multiparametric prostate MRI (mpMRI) sequences—T2W, diffusion-weighted imaging (DWI) and apparent diffusion coefficient (ADC), and dynamic contrast-enhanced (DCE)—in assessing prostate cancer (PCa) index lesion volume using whole-mount pathology as the ground-truth; to assess the impact of an endorectal coil (ERC) on the measurements. Materials and Methods: We retrospectively enrolled 72 PCa patients who underwent 3T mpMRI with (n = 39) or without (n = 33) an ERC. A pathologist drew the index lesion borders on whole-mount pathology using planimetry (whole-mountvol ). A radiologist drew the borders of the index lesion on each mpMRI sequence—T2Wvol, DWIvol, ADCvol, and DCEvol . Additionally, we calculated the maximum index lesion volume for each patient (maxMRIvol ). The correlation and differences between mpMRI and whole-mount pathology in measuring the index lesion volume and the impact of an ERC were investigated. Results: The median T2Wvol, DWIvol, ADCvol, DCEvol, and maxMRIvol were 0.68 cm 3, 0.97 cm 3, 0.98 cm 3, 0.82 cm 3, and 1.13 cm 3 . There were good positive correlations between whole-mountvol and mpMRI sequences. However, all mpMRI-derived volumes underestimated the median whole-mountvol volume of 1.97 cm 3 (P ≤ 0.001), with T2Wvol having the largest volumetric underestimation while DWIvol and ADCvol having the smallest. The mean relative index lesion volume underestimations of maxMRIvol were 39.16% ± 32.58% and 7.65% ± 51.91% with and without an ERC (P = 0.002). Conclusion: T2Wvol, DWIvol, ADCvol, DCEvol, and maxMRIvol substantially underestimate PCa index lesion volume compared with whole-mount pathology, with T2Wvol having the largest volume underestimation. Additionally, using an ERC exacerbates the volume underestimation.